2012
DOI: 10.1111/cns.12018
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Upregulates High Mobility Group Box‐1 and Disrupts the Blood–Brain Barrier causing Cognitive Dysfunction in Aged Rats

Abstract: HMGB1 and RAGE signaling appear pivotal mediators of surgery-induced cognitive decline and may contribute to the changes in BBB permeability after peripheral surgical trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(132 citation statements)
references
References 49 publications
5
127
0
Order By: Relevance
“…The MWM test was used to evaluate the learning and memory of rats. A computerized video track system (Logitech, Suzhou, China) was used to record the movement of the rats in the water maze by following a previous method (13). Briefly, a transparent circular platform was placed below the water surface of the southeast quadrant in a circular black pool.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MWM test was used to evaluate the learning and memory of rats. A computerized video track system (Logitech, Suzhou, China) was used to record the movement of the rats in the water maze by following a previous method (13). Briefly, a transparent circular platform was placed below the water surface of the southeast quadrant in a circular black pool.…”
Section: Methodsmentioning
confidence: 99%
“…These showed that ROCK2 was closely involved in the neurotoxicity of sevoflurane. Neurotoxicity of anesthetics was well reported in aged animals (13)(14)(15), natal animals (15) and cultured neurons (16). Yan et al (17) showed that the isoflurane-induced decrease of nNOS is closely correlated with the cognitive impairment in aged rats.…”
Section: Rhoa and Rock2 Upregulation Of Rat Hippocampus Is Involved Imentioning
confidence: 99%
“…Co-application of multiple anesthetics (midazolam, nitrous oxide and isoflurane) in 7-day old mice caused widespread apoptosis and degenerative changes in central nervous system and subsequent impairment of learning and memory in their adulthood (Jevtovic-Todorovic et al, 2003). In aged rats, isoflurane anesthesia induced weak and temporary cognitive deficit (He et al, 2012). Surgical trauma plus anesthesia, especially major surgery, causes more severe POCD.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical trauma plus anesthesia, especially major surgery, causes more severe POCD. Numerous reports showed that splenectomy, which greatly alters circular system and immune system, resulted in severe cognitive dysfunction in elder rats and mice He et al, 2012;Kamer et al, 2012). Thus, splenectomy is frequently used as major surgery trauma in research involving POCD (Wan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral cytokines, including alarmins like HMGB-1, mediate and facilitate the migration of macrophages into the brain parenchyma through activation of TNF-α/NF-κB signaling pathway and impairing BBB function, which may consequently affect memory and cognitive function (30,53). HMGB-1 has recently been shown to be associated with BBB dysfunction after abdominal surgery and its effect on macrophages have been proven to be related to the processes of surgery-induced cognitive decline and long-term neurocognitive function after sepsis (39,40,54). Aside from a direct effect of pro-inflammatory cytokines on the endothelium, comorbidities including advanced age, systemic diseases, and infections can further impact on the BBB integrity and permeability (55).…”
Section: Volume 1 November 2014mentioning
confidence: 99%